Analysis of Post Operative Taste Disturbance Following Mastoid Surgery - Maharjan, R; Shrivastav, RP (Nepalese Journal of ENT Head and Neck Surgery, 2013)
Nepalese Journal of ENT Head and Neck Surgery, Vol. 3 Issue 1 (Jan-June 2012) Page 7-8 DOI: http://dx.doi.org/10.3126/njenthns.v3i1.8179